Types of patients in a psychiatric intensive care unit - Wynaden, Dianne; McGowan, S.; Chapman, Rose; Castle, D.; Lau, P.; Headford, C.; Finn, M. (Taylor & Francis Ltd., 2001)
Objective: This paper reports the findings of a descriptive study of a patient populationover a three-month period on an eight bed psychiatric intensive care unit (PICU) in Western Australia. The report provides a quantitative insight into the profile of patients in PICUs. It provides information on patients' diagnoses, presenting signs, symptoms and/or behaviours,legal codes assigned to patients, treatment interventions and management. Method: Data were collected prospectively from August to October 1999. A total of 122 patients were admitted to the PICU during the review period. Data were entered into an Access program then exported to SPSS (Version 9 for Windows) for analysis and frequency distributions were obtained. Results: The results confirmed that the majority of patients admitted to the PICU were assessed as a high level of risk or needed containment. This finding is in line with the admission criteria developed by staff working in the PICU. It also supports the view that staffworking in these units require expertise and confidence to communicate with and manage potentially aggressive and highly aroused patients. Conclusion: This study demonstrates the importance of ongoing evaluations of patient populations in promoting best practice initiatives in psychiatric care.